Nomogram for predicting spontaneous pregnancy after microscopic varicocelectomy in infertile men with normal hormone - Lina Liu; Jia Li; Gang Liu; Chunyu Pan; Song Bai; Yunhong Zhan; Liping Shan (BMC Pregnancy and Childbirth, 2022)
Abstract Introduction The current challenge for the treatment of varicocele is identifying patients who could benefit the most from surgery. We aimed to develop and validate a nomogram for predicting spontaneous pregnancy following microscopic varicocelectomy in infertile men, based on a large cohort. Methods Two hundred eighty-two consecutive patients who underwent microscopic varicocelectomy from January 2018 to December 2020 were enrolled as participants in the study. Xiang Hua center (206 patients) as a development cohort. Hu Nan center (76 patients) as a validation cohort. Patient clinicopathologic data were recorded. Multivariate logistic regression was used to build a predictive model with regression coefficients. Then, backward stepwise selection was applied, and the likelihood ratio test with Akaike’s information criterion was used as the stopping rule. The performance of this predictive model was assessed for discrimination, calibration, and clinical usefulness. Results Predictors of this model included the age of female partners, diameter of veins, initial and increased total progressively motile sperm count. The model demonstrated good discrimination with an AUROC of 0.925 (p < 0.001) and calibration (Unreliability test, p = 0.522) in the validation cohort. Furthermore, the model was clinically useful, according to decision curve analysis. Conclusions Our findings indicated that younger female partners, larger diameter of veins, higher initial and increased total progressively motile sperm count were significant predictors of spontaneous pregnancy in infertile men, post microscopic varicocelectomy. This nomogram may assist in individual decision-making on the treatment strategy of varicocele preoperatively and improve the treatment outcome.